Proyeksi Penduduk Menuju Indonesia Emas Tahun 2045 Melalui Penerapan Teori Malthus - Milda Nur Risma Abdah; Fatimah Aqilah Ichtiari; Anisara Aulia (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
This research aims to analyze the truth value of the circulation of population theory issues in Indonesia regarding the demographic bonus and Golden Indonesia based on combination of Malthusian theory and its refutation by Karl Marx. This research method is quantitative research and the Geometric Method is a scientific calculation based on the components of population growth rate. Malthus's theory states that the rate of population growth follows a geometric progression, so the Geometric Method is used to present population projection data. Then the projection data that has been obtained is analyzed for its relevance to the issue of Golden Indonesia 2045 where the government agrees that Indonesia is targeted to become a developed country by the 100th year of its independence. Based on research, it can be seen that Indonesia's productive age population will reach its maximum number in 2045 when compared with previous years. The demographic bonus that will occur in Indonesia, if used optimally, will have a positive influence on the economy, as Karl Marx's refutation of Malthus's theory states that population growth will refer more to the quality of human resources and the availability of employment opportunities, in order to realize the Golden Indonesia in 2045.